High N2O consumption potential of weakly disturbed fen mires with dissimilar denitrifier community structure - Buchen, C.; Roobroeck, D.; Augustin, J.; Behrendt, U.; Boeckx, P.; Ulrich, A. (Elsevier, 2019)
Peat soils can be strong sources of atmospheric nitrous oxide (N2O), but at the same time act as sinks for the greenhouse gas N2O. However, the role of N2O reduction to dinitrogen (N2) here is still not fully understood. In particular, this applies to pristine or weakly disturbed fen mires. These types of peatland ecosystems are characterised by anoxic soil conditions and special N dynamics restricted to ammonium (NH4+) turnover and very low nitrate (NO3−) availability. N2O and N2 fluxes from intact soil cores from three weakly disturbed fen mire types and two soil habitats (tussocks and hollows) were investigated using the helium (He) incubation approach. Ambient air in headspaces were first substituted with a He-O2 trace gas mixture to quantify N2O and N2 exchanges under prevailing soil oxygen (O2) conditions, and then with an anoxic He trace gas mixture (99.9% He) for establishing the maximum possible denitrification rate. Changing from the He-O2 mixture to a pure He trace gas mixture led to strong increase of N2 fluxes (up to 2916 μg N m−2 h−1) and negative N2O fluxes of up to −72 μg N m−2 h−1. Whilst small differences in N gas fluxes were found between all types of fen mires, an analysis of the denitrifier abundance based on nirK, nirS and nosZ genes indicated respectively more pronounced variation. The structure of denitrifier communities exhibited a strong plot specificity driven by water-filled pore space, soil organic matter and soil pH. This short-term He incubation experiment revealed that weakly disturbed fen mires act as considerable N2O sinks under anoxic conditions and improved our knowledge of the original N dynamics in this peatland ecosystem.